2019
DOI: 10.1128/jvi.01248-19
|View full text |Cite
|
Sign up to set email alerts
|

Porcine RING Finger Protein 114 Inhibits Classical Swine Fever Virus Replication via K27-Linked Polyubiquitination of Viral NS4B

Abstract: Porcine RING finger protein 114 (pRNF114) is a member of the RING domain E3 ligases. In this study, it was shown that pRNF114 is a potential anti-CSFV factor and the anti-CSFV effect of pRNF114 depends on its E3 ligase activity. Notably, pRNF114 targets and catalyzes the K27-linked polyubiquitination of the NS4B protein and then promotes proteasome-dependent degradation of NS4B, inhibiting the replication of CSFV. To our knowledge, pRNF114 is the first E3 ligase to be identified as being involved in anti-CSFV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It has been suggested that K27-linked ubiquitination of NS3 enhances protein–protein interactions and facilitates the formation of the NS2B3 complex [ 89 ]. However, this is a rather unexpected finding since this non-canonical ubiquitination has been previously shown to inhibit viral replication by promoting the proteasomal degradation of viral proteins from classical swine fever and porcine reproductive and respiratory syndrome viruses [ 90 , 91 ]. Further experiments will be required to shed more light on K27-linked ubiquitination of viral proteins.…”
Section: Lysine 27—a Major Player Of Innate Immunitymentioning
confidence: 99%
“…It has been suggested that K27-linked ubiquitination of NS3 enhances protein–protein interactions and facilitates the formation of the NS2B3 complex [ 89 ]. However, this is a rather unexpected finding since this non-canonical ubiquitination has been previously shown to inhibit viral replication by promoting the proteasomal degradation of viral proteins from classical swine fever and porcine reproductive and respiratory syndrome viruses [ 90 , 91 ]. Further experiments will be required to shed more light on K27-linked ubiquitination of viral proteins.…”
Section: Lysine 27—a Major Player Of Innate Immunitymentioning
confidence: 99%
“…The RING finger protein family is widespread and functionally conserved in eukaryotes, from yeast to animals. The roles implicated in growth, oxidative stresses tolerance, response to the pathogen and signal transduction (Ardley, 2009;An et al, 2017;Zhang et al, 2019). Rfp17 was annotated to be involved in gamete generation in our results.…”
Section: The Key Dmgs Involved In Reproduction Morphology and Visiomentioning
confidence: 78%
“…PARP10 is ubiquitinated by RNF114 via K27-linked polyubiquitination, which enhances PARP10 enzymatic activity. More recently, porcine RNF114 was found to inhibit classical swine fever virus (CSFV) replication via the K27-linked polyubiquitination of viral NS4B [36]. These results indicate that RNF114-mediated polyubiquitination is complicated and that RNF114 may regulate substrate stability and activity.…”
Section: Discussionmentioning
confidence: 99%